Post Vaccination Immunity Status Against Hepatitis B Virus Infection-An Analytical Study (Journal of Dhaka National Medical College & Hospital, 2020)
Introduction: Hepatitis B vaccine has shown to be highly efficacious in preventing hepatitis B virus (HBV infection). Immunization with this vaccine reduces the subsequent development of chronic hepatitis B in young children from perinatal or early childhood exposure to HBV.8.9 However, the duration of satisfactory protection level conferred by hepatitis B vaccination is not well understood. 10,11 Previous thinking was that this vaccination would provide effective coverage for five to seven years. 12,13 But subsequently it has been proved that it offers long-term immunity. Methods: This is a cross sectional observational study. All the patients were collected among the admitted patients of Paediatric ward, Dhaka National Medical College (DNMC) from January to December, 2019.Result: This study reveals 49.12% children have developed adequate immunity i.e. Anti-HBs antibody level >100 mIU/ml, and 38.60% showed poor response (10-100 mIU/ml). Only 12.28% are nonresponsive. Poor responders also having satisfactory immunity, may be for a shorter period. Difference of immunity level developed between two groups, 1 yr. - 6yrs and > 6 yrs. -12 yrs. is obvious. The reason is not very clear. More elaborate studies are required to probe on these facts. Conclusion: Acquisition of acceptable immunity level following our vaccination schedule is satisfactory (87.72%). Larger study should be conducted to develop a consensus of opinion.J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 23-27